2009
DOI: 10.1016/j.rmed.2009.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Smoking cessation in chronic obstructive pulmonary disease

Abstract: Chronic obstructive pulmonary disease (COPD) is increasing in prevalence, and is predicted to become the third leading cause of deaths worldwide by 2020. The precise prevalence of COPD is not known, as many individuals with the disease are left undiagnosed, despite the requirement of only simple spirometry testing for disease detection. The major risk factor for the development of COPD is cigarette smoking, with 90% of deaths from COPD directly attributable to smoking. Therefore smoking cessation is the most e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 67 publications
2
80
0
1
Order By: Relevance
“…This should elicit a response and open discussion regarding the dangers of continuing cigarette smoking. Referral to support groups, educational and counselling sessions, and the use of newer pharmaceuticals all offer avenues for success [8,9,20,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…This should elicit a response and open discussion regarding the dangers of continuing cigarette smoking. Referral to support groups, educational and counselling sessions, and the use of newer pharmaceuticals all offer avenues for success [8,9,20,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that multicomponent cessation programs wherein health care providers combine counseling with pharmacotherapy, ongoing support, and follow-up when needed can further improve cessation rates. It was reported that counseling, pharmacotherapy treatments, and NRT are also effective (53,119,124,127,133). According to two independent systematic reviews by Warnier et al (135) and van der Meer et al (129), pharmacological and behavioral (psychosocial) intervention was more effective than no intervention.…”
Section: Tobacco Treatment Strategies In Copd-targeting Stimulusmentioning
confidence: 99%
“…As a result, continued tobacco use can lead to millions of deaths and billions of dollars in estimated healthcare costs. Accordingly, an estimated 90% of all deaths from COPD can be attributed to CS (124). Research has shown that early smoking cessation alleviates the progression of this debilitating pulmonary disease (8,9,107).…”
mentioning
confidence: 99%
“…nicotine replacement therapy, varenicline, bupropion) should be combined with strong motivation. A study conducted by Tashkin and Murray [13] in the Netherlands reported a 42% smoking cessation rate in one year among smoking patients with COPD; however, this rate was reported to be 68% in patients without COPD. In another study conducted by the same author, smoking cessation rate was lower in females with COPD due to fear of weight gain, compared to male patients.…”
Section: Discussionmentioning
confidence: 97%